Residential Network of Franz Joseph Czernin of Chudenitz in Vienna and Prague in the 1720s and the 1730s of the 18th Century (Theatrum historiae, 2019)
This study deals with the residential network of Franz Joseph Czernin of Chudenitz (1697–1733), namely the urban part of this network. Czech count Czernin possessed many buildings in the capital cities of the historical lands of the Habsburg monarchy (eight in Prague, three in Vienna). Our goal is to discover this network and put it in the context of residential networks of Bohemian aristocrats in this period.
Keywords: early modern age; Bohemian aristocracy; residential networks; Franz Joseph Czernin of Chudenitz; 18th century